Correction: A durable monolithic polymer foam for efficient solar steam generation. Issue 5 (23rd January 2018) - Chen, Qiaomei; Pei, Zhiqiang; Xu, Yanshuang; Li, Zhen; Yang, Yang; Wei, Yen; Ji, Yan
Abstract : Correction for 'A durable monolithic polymer foam for efficient solar steam generation' by Qiaomei Chen et al., Chem. Sci., 2018, DOI: ; Web:10.1039/c7sc02967e .